2019
DOI: 10.1029/2018jg004513
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Hydrological Changes on Nutrient Transport From Diffuse Sources in a Rural River Basin, Western Japan

Abstract: Increased frequency of heavy rainfall caused by climate change may affect nutrient transport from forests and agricultural lands into downstream rivers. However, little information is available on how the effects of land cover on nutrient concentrations in the downstream rivers change depending on hydrological conditions. To elucidate this, we investigated the effects of changes in precipitation and river discharge on the relationship between river nutrient concentrations (total nitrogen, total phosphorus, nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…This topic can also be discussed in the framework of stochastic control with partial observation, and will be addressed utilizing analytical and numerical techniques related to degenerate parabolic PDEs. From an application viewpoint, a complicated population dynamics model considering more detailed environmental dependence may be employed, 99‐101 which would be investigated along with extensive laboratorial experiments on the algae detachment. A key challenge would be how to formulate a more sophisticated model without using unnecessarily complex coefficients.…”
Section: Discussionmentioning
confidence: 99%
“…This topic can also be discussed in the framework of stochastic control with partial observation, and will be addressed utilizing analytical and numerical techniques related to degenerate parabolic PDEs. From an application viewpoint, a complicated population dynamics model considering more detailed environmental dependence may be employed, 99‐101 which would be investigated along with extensive laboratorial experiments on the algae detachment. A key challenge would be how to formulate a more sophisticated model without using unnecessarily complex coefficients.…”
Section: Discussionmentioning
confidence: 99%
“…Jarvis, . Moreover, urban areas can contribute to P pollution because there is a positive correlation reported between P content and urban land use (Brett et al, 2005;Ide et al, 2019). Urbanization is typically associated with modifications of physical and hydrogeological characteristics of basins and creation of nutrient sources.…”
Section: Core Ideasmentioning
confidence: 99%
“…Yard fertilizers, septic tank drainage, domestic animal wastes, and elevated soil erosion in urban areas are commonly linked to high P content and consequently water quality degradation (Carpenter et al, 1998;Soranno, Hubler, Carpenter, & Lathrop, 1996;Tufford, McKellar, & Hussey, 1998). In contrast, Brett et al (2005) and Ide et al (2019) found that the average P concentration was negatively correlated with forest area ratio. The loss of forests in humid areas leads to minimizing the recycling of nutrients owing to declining microbial activities and plant processes that immobilize nutrients in the forest canopy, organic matter, and soil (Abelho, 2001;Wahl, McKellar, & Williams, 1997).…”
Section: Core Ideasmentioning
confidence: 99%
See 1 more Smart Citation
“…We focus on a mathematical modeling of monitoring a continuous‐time process representing temporal evolution of some environmental and ecological indices. We assume that the monitoring is carried out in a discrete‐time manner as in real problems of environment and ecology 12‐19 . The decision‐maker, the observer of the target process, decides a monitoring policy containing the times at which the observations are carried out.…”
Section: Introductionmentioning
confidence: 99%